Effects of serial and acute enteric-coated sodium bicarbonate supplementation on anaerobic performance, physiological profile, and metabolomics in healthy young men - Zhou, Nihong; Fan, Yongzhao; Kong, Xiaoyang; Wang, Xiangyu; Wang, Junde; Wu, Hao (Frontiers in Nutrition, 2022)
Background Previous studies have reported that sodium bicarbonate ingestion may enhance high-intensity exercise performance and cause severe gastrointestinal distress. However, enteric-coated sodium bicarbonate may reduce gastrointestinal symptoms of sodium bicarbonate after oral administration. This remains to be confirmed. This study aimed to verify the effects of serial and acute enteric-coated sodium bicarbonate supplementation on anaerobic performance, physiological profile, and metabolomics in healthy young men. Methods Healthy young males (n = 12) ingested 0.2 g/kg body mass of enteric-coated sodium bicarbonate (ES) in serial enteric-coated sodium bicarbonate (SES, continuous ES supplementation for 5 days) and acute enteric-coated sodium bicarbonate (AES, acute ES supplementation before exercise) or a placebo (PL) in a randomized crossover design. After each supplement protocol, the participants completed four Wingate anaerobic tests (WAT). The first three Wingate tests (testing anaerobic capacity) were performed with a 5-min passive recovery between each. After the third Wingate test, participants were required to complete a 50-min recovery followed by a fourth WAT test (testing the recovery of anaerobic capacity after 50-min intervals). Blood lactate (BLA), heart rate (HR), and ratings of perceived exertion (RPE) were measured in all conditions during the test, as was the subjective gastrointestinal–symptoms assessment questionnaire (GSAQ). Mean power (MP) and peak power (PP) were recorded after four WATs. Urine samples were collected before the test and 50 min after the 3rd WAT. Results Serial enteric-coated sodium bicarbonate supplementation improved anaerobic capacity in the third bout of WATs, as observed based on an increase in mean power (SES vs. PL (613 ± 57 vs. 542 ± 64 W), P = 0.024) and peak power (SES vs. PL (1,071 ± 149 vs. 905 ± 150 W), P = 0.016). Acute ES supplementation did not affect anaerobic capacity. The occurrence of gastrointestinal symptoms after enteric-coated sodium bicarbonate supplementation was minimal and no difference compared to placebo in the current study. In particular, serial enteric-coated sodium bicarbonate supplementation had no gastrointestinal side effects before the test. The AES and SES groups had a trivial effect on blood lactate compared to the PLA group. There was no significant difference in HR and RPE among the three groups. Based on targeted metabolomics analysis, the 50 min after the third WAT, the levels of lactate (P < 0.001), L-Malic acid (P < 0.05), and oxaloacetate (P < 0.05) were significantly higher in the SES group than in the PL group. Compared with the AES group, the levels of lactate and fumarate in the SES group were significantly increased (P < 0.05). Conclusions Our study indicates that serial enteric-coated sodium bicarbonate supplementation positively improves anaerobic performance among healthy young men. However, acute ingestion of enteric-coated sodium bicarbonate did not improve anaerobic exercise performance. Either with serial or acute supplementation doses, enteric-coated sodium bicarbonate produced fewer gastrointestinal symptoms and no difference compared to placebo, especially with no gastrointestinal side effects after serial supplementation. Serial and acute supplementation of enteric-coated sodium bicarbonate might tend to promote lactate clearance. Furthermore, serial enteric-coated sodium bicarbonate ingestion may cause changes in the metabolism of lactate, L-Malic acid, oxaloacetate, and fumarate 50 min after exercise, which presumably may promote the tricarboxylic acid cycle and lactate clearance.